The difficult intraoperative nasogastric tube intubation: A review of the literature and a novel approach - Ching, Yiu-Hei (SAGE Open Med, 2014)
Nasogastric tube intubation of a patient under general anesthesia with an endotracheal tube in place can pose a challenge to the most experienced anesthesiologist. Physiologic and pathologic variations in a patient’s functional anatomy can present further difficulty. While numerous techniques to the difficult nasogastric tube intubation have been described, there is no consensus for a standard approach. Therefore, selecting the most appropriate approach requires a working knowledge of the techniques available, mindful consideration of individual patient and clinical factors, and the operator’s experience and preference. This article reviews the relevant literature regarding various approaches to the difficult nasogastric tube intubation with descriptions of techniques and results from comparative studies if available. Additionally, we present a novel approach using a retrograde technique for the difficult intraoperative nasogastric tube intubation.